MENTAL DISTRESS DURING THE PUERPERIUM: THE NURSING TEAM'S KNOWLEDGE - Brito, Ana Paula Almeida; Paes, Sarha de Oliveira Gonçalves; Feliciano, Welington Luis Lima; Riesco, Maria Luiza Gonzalez (Cogitare Enfermagem, 2022)
Objective: to assess the Rooming-In Nursing team’s knowledge about mental distress during the puerperium and to offer subsidies for educational actions. Method: a descriptive and quantitative study carried out with 30 Nursing professionals from a public teaching hospital in São Paulo, Brazil. The data were collected between December 2020 and January 2021 using a structured questionnaire and analyzed descriptively. Results: 73.3% of the nursemidwives, nurses, and nursing technicians and assistants were aged ≥40 years old, and 80% had more than five years of working time. There was a predominance of knowledge about the role of Nursing and its respective practices in the assistance provided in cases of mental distress during the puerperium (majority of expected answers in 80% of the questions), in contrast to the knowledge about pathophysiology, symptoms and causes of puerperal blues, depression and psychosis (majority of expected answers in 40% of the questions). Conclusion: the results can support permanent education, aiming to expand the Nursing team’s knowledge and strengthen the care process.